Aptamer and rolling circle amplification-involved sandwich assay for platelet-derived growth factor-BB with absorbance analysis. Issue 5 (22nd January 2015) - Lv, Li; Guo, Limin; Zhao, Qiang
Abstract : An aptamer-based absorbance assay for PDGF-BB was developed by combining rolling circle amplification reaction and catalysis with horseradish peroxidase. Abstract : This paper described an aptamer-based absorbance assay combining rolling circle amplification (RCA) for platelet-derived growth factor-BB (PDGF-BB). PDGF-BB was specifically captured by an antibody on a microplate, and then bound with an anti-PDGF-BB aptamer connected with a primer sequence, forming a sandwich complex. The primer sequence was extended by RCA reaction to generate a long single-stranded DNA with repeated copies. The amplified DNA product was hybridized with many biotinylated short DNA probes, and then labeled with streptavidin–horseradish peroxidase conjugate (SA–HRP). The HRP catalyzed the conversion of a substrate to a colored product, which was measured by simple absorbance analysis to achieve the detection of PDGF-BB. By involving RCA and HRP catalysis amplification, sensitive detection of PDGF-BB with a good selectivity was obtained; the detection limit reached 3.1 pM.